Revolutionizing Endodontics: Potential, Challenges and Ethical Concerns of CRISPR Technology in Endodontics - Isma Sajjad; Mustafa Sajid; Syed Yawar Ali Abidi; Maham Muneeb Lone (ziauddin University, 2024)
In the evolving landscape of endodontic therapy, our primary objective revolved around maintaining dental pulp vitality or intervening effectively when the pulp is irreparably damaged or infected. At the forefront of these groundbreaking advancements stands CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) gene-editing technology that has captivated the global scientific community. The origins of CRISPR hail from a natural defense mechanism employed by bacteria and archaea. These microorganisms capture snippets of DNA from invading viruses, creating a genomic library that serves as a historical record of past viral encounters. This remarkable natural process has paved the way for potentially transformative methods in treating a spectrum of dental pulp diseases and disorders. However, integrating CRISPR into clinical practice is not without its complexities and moral dilemmas. One of the foremost concerns is the reliability of the gene-editing process. To address this, there is a concerted effort within the scientific fraternity to refine the Cas9 enzyme further, to enhance the design of guide RNAs, and to develop sophisticated techniques for identifying and rectifying any inadvertent genetic modifications. In summary, the horizon of endodontic therapy is becoming increasingly promising, with CRISPR technology leading the charge. Hence, the objective of this review article was to provide a comprehensive overview of the potential, challenges, and ethical concerns of using CRISPR technology in the field of endodontics. Keywords: Endodontics, CRISPR, Cas-9 Systems, Gene Editing, Genetic Engineering.